2019
DOI: 10.1021/acschembio.9b00745
|View full text |Cite|
|
Sign up to set email alerts
|

Dimensionally Enhanced Antibacterial Library Screening

Abstract: The emergence and spread of antimicrobial resistance is a major public health threat, and there is an urgent need to develop new strategies to address the issue. In this study, the possibility of enhancing a whole cell based antibacterial library screen by increasing the dimensionality of the screening effort is explored using methicillin-resistant Staphylococcus aureus (MRSA) as the target organism. One dimension involved generating and screening a human liver microsome metabolized FDA approved drug library. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 35 publications
0
35
2
Order By: Relevance
“…In a prior study, we demonstrated in MRSA how a two-dimensional screening strategy comparing an unmetabolized (UM) versus postmetabolized (PM) FDA library screen combined with a −/+ resistant-to antibiotic screen could enhance the ability to identify new agents and new synergistic combinations ( 23 , 32 ). This study identified gemcitabine as having generally good anti-MRSA activity, identified strong synergy between cefoxitin and floxuridine against MRSA, and also identified capecitabine as having several anti-MRSA metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prior study, we demonstrated in MRSA how a two-dimensional screening strategy comparing an unmetabolized (UM) versus postmetabolized (PM) FDA library screen combined with a −/+ resistant-to antibiotic screen could enhance the ability to identify new agents and new synergistic combinations ( 23 , 32 ). This study identified gemcitabine as having generally good anti-MRSA activity, identified strong synergy between cefoxitin and floxuridine against MRSA, and also identified capecitabine as having several anti-MRSA metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Many drugs are also known to have active metabolites ( 21 , 22 ). Comparative screening of the unmetabolized (UM) and postmetabolized (PM) libraries allows agents with increased antibacterial activity to be identified for deconvolution and active metabolite identification, as recently demonstrated using a human liver microsome-metabolized FDA-approved drug library ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for S. aureus to evolve resistance to capecitabine is not practical to test in broth culture, because S. aureus is not growth inhibited by capecitabine at concentrations up to 200 μ M ( 39 ). However, S. aureus 5-FU-resistant isolates evolved in MHB harbor mutations in genes consistent with the roles of 5-FU in disrupting DNA and RNA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Capecitabine was developed in the late 1990s and is used to treat colon, breast, and gastric cancers ( 21 , 37 , 38 ). It is not by itself considered antibacterial and requires three metabolic steps for conversion to 5-FU ( 29 , 39 ). To validate the identification of capecitabine as an inhibitor of S. Typhimurium growth, we compared growth in the presence of capecitabine in the minimal medium versus a rich medium.…”
mentioning
confidence: 99%